Mineral, seed morphology, and agronomic characteristics of proso millet grown in the inland Pacific Northwest - Reinman, Tayler; Braden, Jessica; Miller, Nathan Daniel; Murphy, Kevin M. (Frontiers in Nutrition, 2024)
Climate change increases stressors that will challenge the resiliency of global agricultural production. Just three crops, wheat, maize, and rice, are estimated to sustain 50% of the caloric demand of the world population, meaning that significant loss of any of these crops would threaten global food security. Increasing cropping system diversity can create a more resilient food system. One crop that could add diversity to wheat-dominated cropping systems in the inland Pacific Northwest is proso millet, a climate-resilient, small-seeded cereal crop that is highly water efficient, able to grow in low fertility soils, and has a desirable nutritional profile. Proso millet shows potential for adoption in this region due to its short growing season, compatibility with regional equipment, and environmental requirements, however US cultivars have been developed for the Great Plains and little research has been conducted outside of this region. To better understand the potential for adoption in the inland PNW, seven commercially available varieties were planted in a researcher-run trial in Pullman, WA and in a series of producer-run trials across the region in 2022. Samples were analyzed for mineral concentration (Zn, Fe, Cu, Mn, Mg, Ca, P, and K), seed morphology phenotypes (seed area, seed eccentricity, thousand seed weight, and seed color), and agronomic phenotypes (grain yield, plant height, days to heading, days to maturity, and percent emergence). Varieties from the researcher-run trial showed significant differences for all traits excluding percent emergence. Samples from producer-run trials showed differences by location for concentration of all minerals and for all seed morphology traits but were not analyzed for agronomic phenotypes. Samples from producer-run trials showed no difference by variety for mineral concentration but showed varietal differences for all seed morphology phenotypes. Most minerals were positively correlated with one another (0.28